PENGARUH BAP DAN KASEIN HIDROLISAT TERHADAP PERTUMBUHAN TUNAS MELON (Cucumis melo L.) SECARA IN VITRO - Istiningdyah, Andini; Tambing, Yohanis; Bustami, Mirni Ulfa (AGROTEKBIS, 2013)
Melon (Cucumis melo L. ) is a horticultural crop that is quite popular in Indonesia . Good taste and nutritional content makes melon increasingly popular with the public . However , often the continuity of supply in the market is still limited. This is due partly because farmers in Indonesia are still planting using seeds imported melons which is quite expensive. Therefore, an effort that can be done to reduce dependence on imported seed is seed multiplication through tissue culture techniques . The growth in tissue culture plantsÂ is controlled by the addition of plant growth regulators . This study aims to determine the effect of BAP and casein hydrolyzate Â for better shoot growth in vitro melon . This research has been carried out in the Laboratory of Plant Biotechnology , Faculty of Agriculture , University Tadulako , Palu . Starting from August to November 2012 . The study design using completely randomized design ( CRD ) Factorial pattern of two factors . The first factor is the concentration of BAP ( 0.25 mg / l , 0,50 mg / l and 0.75 mg / l ) , the second factor is the concentration of casein hydrolyzate ( 150 mg / l , 200 mg / l and 250 mg / l ) . significant treatment effect , Further tests using the Test Honestly Significant Difference ( HSD ) at the 5% level . The results of this study indicate that the use of media with different compositions lead to different effects on the growth of shoots melons . Treatment of 0.50 mg / l BAP + 150 mg / l casein hydrolyzate gives a better effect on plant height, number of shoots and number of leaves